Pérdidas de sacarosa en el proceso de elaboración de panela (1978)
Sucrose losses in the industry of unrefined brown sugar paste (panela) are due to a number of different situations, before and within the process as well. When sugar cane in stored for a period of 5 days it losses approximately 7.48'14 of its own weight and about 10% of the total sucrose content. During the process, sucrose losses take place in the extraction of the juice and its cleaning and also in the invertion to a reduced sugar when water evaporation and sugar concentration are ocurring. These losses are about 30% of the total sucrose content.